REPOSISI SEKTOR KELAUTAN DAN PERIKANAN DALAM PEREKONOMIAN NASIONAL - Santoso Santoso; John Haluan; Kooswardhono Mudikdjo; Akhmad Fauzi (Buletin PSP, 2008)
Each input of economic development of marine and fisheries activities able to be measured/evaluated its works more interrelated with its input, output, outcome and its impact related with its contribution in national economics matters. Recently, the position of marine and fisheries in national development and economic has not at the position which able to be evaluated its works yet since formally it has not be inserted in national economic/ Gross Domestic Products (GDP). In other hand, the establishment of marine and fisheries department that has get fund from National budget (APBN) to manage and facilitate of marine and fisheries management able to be measured for its impact for national economics matters. The aimed of this research is to analyze the factors related with above matters consists of : VA, sub-sector of marine potential, perception of official and capacity building.The result of this research shows that inclusion of marine and fisheries sector in Gross Domestic Products (PDB) able to do that are : firstly, separate fisheries sub-sector from agriculture sector and then put in the marine and fisheries sector, secondly, potential of marine resources has high economics value to product such as coastal water has NPV USD 69.5 and IRR 30%. Thirdly, placement of marine and fisheries sector in PDB has supporting from related official but it needed to be supported by rearrangement of DKP structure organization.